Developing Scientific Practices in Primary School: Benzene Ring Heuristic (BRH) Application - Gokbulak, Yagmur; Senler, Burcu (Universitas Pendidikan Indonesia, 2021)
This study aims to develop primary-school studentsâ€™ understanding of the scientific practices in the Benzene Ring Heuristic (BRH) and to determine how BRH applications would affect student perceptions about science, scientific knowledge, and scientists. An interpretative qualitative research design was used in the study. The study group consisted of 9 fourth-grade students (6 girls, 3 boys) in a public primary school. To identify the studentsâ€™ thoughts and perceptions about science, scientific knowledge, and scientists, the study employed open-ended questions as well as the â€œDraw-a-Scientist Testâ€. In addition, a poster activity was used to determine how well students understood the scientific practices in the BRH. The drawing test results showed that students drew scientists in general as female, young, most often with a neat-looking physical appearance in enclosed areas mainly representing a laboratory environment, and who is experimenting. An analysis of the posters produced by the students as part of the BRH suggested a certain amount of improvement. These results have educational implications and should be helpful for teachers and teacher educators to better understand the effects of using BRH in science education.